Cultivating Human and Planetary Health in a Time of Social-Ecological Transformation - Zywert, Katharine (University of Waterloo, 2021)
Human health is fundamentally dependent on the health of the Earth’s biophysical systems, but continued dependence on economic growth to pursue social goods is rapidly undermining the ecological foundations of health. If it is impossible to decouple economic growth from ecological destruction at a global scale, securing a sustainable and healthy future will require a transition toward a post-growth political economy that can meet basic needs and enable health and wellbeing within planetary boundaries. This dissertation investigates how health systems in high- income nations might adapt to the social-ecological systems transformations unfolding in the Anthropocene, the epoch of human impact. Based on a series of semi-structured interviews with 51 researchers, health practitioners, and social innovators across diverse fields as well as an extensive literature review, it argues that the approaches that hold the greatest potential to enable human and planetary health in an equitable and sustainable future tend to be found on the margins of health systems. Promising initiatives often depart substantially from the incentive structures, power dynamics, goals, and mindsets that define the current social-ecological regime and do not necessarily align with mainstream sustainability discourses. Instead, they: disrupt dominant ideas about mental health, ageing, chronic illness, and death; circumvent exploitative markets for medications, medical technologies, and professionalized care; attend not only to the health of individual human bodies, but to the health of internal ecologies, human populations, nonhuman species, and the planet as a whole; and embody alternative, more inclusive ways of practicing medicine within communities and ecosystems. This dissertation illustrates the potential of diverse initiatives including care farming, the soil health movement, complexity medicine, family foster care for mental illness, community nursing, mutual aid, and herbalism, among others. Collectively, these initiatives prefigure the kinds of ideas, practices, and structures that could enable post-growth health systems to cultivate human and planetary health in a time of social-ecological transformation.
Keywords: planetary health; health systems; social-ecological systems; ecological economics; degrowth; population health; social innovation